A governança dos riscos das nanotecnologias e o princípio da precaução: um estudo a partir da teoria dialética da rede - Berger Filho, Aírton Guilherme (Universidade do Vale do Rio dos Sinos, 2016)
The object of this academic research is the analysis of plural interactions in the governance of the risks and uncertainties of nanotechnology, from the perspective of dialectic of the law as a network, developed by Ost and Kerchove, focusing on comprehension of multi-dimensional aspects involving the precautionary principle. As a research problem, it is questioned: what is the scope and relevance of applying the precautionary principle, in the dynamic and decentralized scene, in the regulation and governance of (nano)technological risks? The answer comes from two premises: a) the development of nanotechnology operates in “socio-technical networks”, which imposes the need of thinking more in terms of coordination of interests than in control by a centralized and hierarchical right; b) the particularities of nanotechnology are a very complex topic to be approached satisfactorily by reductionist perspectives of Law and Sciences, and it may take very serious risks so that the power of decision is restricted to scientists, politicians, and economic agents. In this context, we support the hypothesis in applying the precautionary principle: a) for being compatible and being present in multiple regulatory strategies, with different normative forces (hard law and soft law), communicating distinct normativity (legal and non-legal), at several levels (from local to global); b) for serving as a foundation to the formation of policies and to decision making, as an action principle anticipated in relation to the scientific uncertainty, in the sense of prudence and democratization of Technoscience. Regardless of the difficulties in applying this principle to emerging technologies, and moved the mistaken view away whereof it is about an abstention principle, we see it as an important mechanism for communicating the duty of care to all the technological governance network, as a “measured action”, in a double sense, both to impose more democratic processes of risks assessment and to guide the decision making in the political sense.
Keywords: Nanotecnologia; Governança dos riscos; Direito transnacional; Rede; Princípio da precaução; Nanotechnology; Risk governance; Transnational law; Network; Precautionary principle; ACCNPQ::Ciências Sociais Aplicadas::Direito